Tocotrienol-Rich Fraction from Rice Bran Demonstrates Potent Radiation Protection Activity. (26th August 2015) - Krager, Kimberly J.; Pineda, E. Nathalie; Kharade, Sujay V.; Kordsmeier, Mary; Howard, Luke; Breen, Philip J.; Compadre, Cesar M.; Hauer-Jensen, Martin; Aykin-Burns, Nukhet
Abstract : The vitamin E analogs δ -tocotrienol (DT3) and γ -tocotrienol (GT3) have significant protective and mitigative capacity against the detrimental effects of ionizing radiation (IR). However, the expense of purification limits their potential use. This study examined the tocotrienol-rich fraction of rice bran (TRFRB) isolated from rice bran deodorizer distillate, a rice oil refinement waste product, to determine its protective effects against IR induced oxidative damage and H2 O2 . Several cell lines were treated with tocotrienols or TRFRB prior to or following exposure to H2 O2 or IR. To determine the radioprotective capacity cells were analyzed for morphology, mitochondrial bioenergetics, clonogenic survival, glutathione oxidation, cell cycle, and migration rate. TRFRB displayed similar antioxidant activity compared to pure tocotrienols. Cells pretreated with TRFRB or DT3 exhibited preserved cell morphology and mitochondrial respiration when exposed to H2 O2 . Oxidized glutathione was decreased in TRFRB treated cells exposed to IR. TRFRB reversed mitochondrial uncoupling and protected cells migration rates following IR exposure. The protective antioxidant capacity of TRFRB treated cells against oxidative injury was similar to that of purified DT3. TRFRB effectively protects normal cells against IR induced injury suggesting that rice bran distillate may be an inexpensive and abundant alternate source.